Influencing Factors on Health Information to Improve Public Health Literacy in the Official WeChat Account of Guangzhou CDC - Ma, Xiaowei; Lu, Jianyun; Liu, Weisi (Frontiers in Public Health, 2021)
Background: social media is used as a new channel for health information. In China, the WeChat official account is becoming the most popular platform for health information dissemination, which gave a good opportunity for the Centers for Disease Control and Preventionto facilitate health information online to improve the public health emergency literacy. Methods: Data were collected from the Guangzhou CDC i-Health WeChat official account between 1 April 1st，2018 and April 30th，2019. Descriptive analysis was performed for the basic information about the followers and posts of our WeChat official account. Multiple logistic regression analysis was used to analyze the association among various factors of posts on engagement of followers of the WeChat official account. Results: Among 187033 followers, the total numbers of page views, shares, likes, add to favorites, and comments for 213 posts were 1147308, 84671, and 5535, respectively. Engagement of followers peaked on the dissemination date and gradually declined. The main post topics were health education posts and original posts. In the multiple logistic regression model, the number of page views was found to be significantly associated with infectious disease posts (AOR: 3.20, 95% CI: 1.16–8.81), original posts (AOR: 10.20, 95% CI: 1.17–89.28), and posts with the title reflected content (AOR: 2.93, 95% CI: 1.16–8.81). Conclusion: Our findings facilitate government to formulate better strategies and improve the effectiveness for public information dissemination.